Orthogonal Analysis on of the Factors Influencing of Ball Screw Roughness and Pitch Deviation - Xie Ru; Li Haolin (Jixie chuandong)
Aiming at the influence of surface roughness and screw pitch deviation on the performance of ball screw,through orthogonal experiment method,the influence factors of grinding wheel speed,trimming feed rate,screw rotation speed and grinding depth on roughness and pitch deviation are explored,the primary and secondary order influencing on the performance of ball screw is determined. The research finding,in the process of grinding,the best combination of various processing parameters for roughness is that the grinding wheel speed takes 1 144 r/min,trimming feed rate takes 208 mm/min,screw rotation speed takes 16 mm/min,grinding depth takes 2 μm. The rank of each parameter variation from its maximum to minimum value is grinding wheel speed,trimming feed rate,screw rotation speed and grinding depth. The best combination of various processing parameters for pitch deviation is that the grinding wheel speed takes 1 144 r/min,trimming feed rate takes 208 mm/min,screw rotation speed takes 16 mm/min,grinding depth takes 1 μm. The rank of importance of each parameter variation from its maximum to minimum value is screw rotation speed,grinding depth,trimming feed rate,grinding wheel speed.